Analisis Rantai Pasok Komoditi Kopra Di Pabrik Pengolahan Kopra PT Samudra Kota Manado - Porang, Theresia Atika; Pakasi, Caroline Betsi Diana; Ngangi, Charles Reijnaldo (AGRI-SOSIOEKONOMI, 2024)
This study aims to determine the supply chain of copra commodities at PT Samudra Manado City. This research was conducted from June to October 2023. Sampling in this study used snowball sampling method (chain method), with a total sample of 17 farmers. This research used primary data and secondary data. The data analysis method used was descriptive analysis to explain the process of product flow, financial flow, and information flow. The results showed that the supply chain at PT Samudra Kota Manado is based on three flows in the supply chain, namely the flow of products from upstream to downstream starting from coconut farmers bringing coconuts to the shelter and then giving them to copra workers to be processed until they become copra. The supply chain of the PT Samudra company is very different from other places, the difference is very clear because in the PT Samudra company the owner controls all parts starting from land leasing, coconut farmers, until the coconut processing stage until it becomes copra, and also to the storage warehouse.